Minority children and academic resilience in the Nordic welfare states. Issue 4 (11th December 2017) - Johnsen, Anja; Ortiz-Barreda, Gaby; Rekkedal, Guro; Iversen, Anette Christine
Abstract : Purpose: The purpose of this paper is to summarise and analyse empirical research on protective factors that promote academic resilience in ethnic minority children mainly aged between 13 and 18 years attending schools in the Nordic countries. Design/methodology/approach: This paper was opted for a literature review of 23 peer-reviewed quantitative articles published between 1999 and 2014. The analysis entailed protective factors at both the personal and environmental levels in ethnic minority children. Findings: Some minority children's school performance may be just as good if not better than majority children when having similar or even lower socioeconomic status than majority children. Protective factors at the personal level included working hard, having a positive attitude towards school, and having high educational aspirations. Protective factors at the environmental level included supportive school systems, supportive schools, and supportive networks including parental qualities and support. The findings are comparable to the findings outside the Nordic countries with one exception; minority children in the Nordic countries performed better than expected despite socioeconomic disadvantages. Research limitations/implications: Protective factors affecting academic resilience need further attention in a time with an increased global migration. Research implications may be related to how schools and policy makers develop supportive school systems, supportive schools, and supportive networks to contribute to making a difference for minority children's educational opportunities in the Nordic countries. Originality/value: Academic resilience is a relatively new research field in the Nordic countries. This review is the first review which has summarised and analysed existing findings on academic resilience in the Nordic countries in minority children.